Pathomorphological differential diagnostic of inflammatory bowel disease in biopsy specimens - Londarydze, V. G. (Запорізький державний медичний університет, 2019)
Inflammatory bowel diseases (IBD) are lifelong disorders that are predominantly observed in developed countries and arise from an interaction between genetic and environmental factors, they include two specific diseases: ulcerative colitis (UC) and Crohn's disease (CD). The diagnostic value of architectural abnormalities and inflammatory features and the differences between UC and CD have been studied extensively. Diagnostic differential can be challenging in some cases. Features which can be used for a proper diagnosis should be clarified.
Keywords: тези доповідей